The impact of a simulated grand tour on sleep, mood, and well-being of competitive cyclists - Lastella, M.; Roach, G. D.; Halson, S. L.; Martin, D. T.; West, N. P.; Sargent, C. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: Professional cycling is considered one of the most demanding of all endurance sports. The three major professional cycling stages races (i.e. Tour de France, Giro d'Italia and Vuelta a España) require cyclists to compete daily covering between ~150-200 km for three consecutive weeks. Anecdotal evidence indicates that such an event has a significant effect on the sleep, mood, and general well-being of cyclists, particularly during the latter stages of the event. The primary aim of this study was to simulate a grand tour and determine the impact a grand tour has on the sleep, mood, and general well-being of competitive cyclists.